Hubungan Antara Employee Engagement Dan Kepuasan Kerja Dengan Kinerja - Mariska, Dhea Dana (Universitas Muhammadiyah Jember, 2018)
Performance is a result of employee behavior to perform tasksÂ according to competence. The Result of employeeâs behavior in performing the duty is the employeeâs attachment to the organization supported by the satisfaction while working. This researches was conduoted on employees of PT K. The number of reserch subjects is 100 people. All subjects work at least 1 year with minimal education DIII and age range 20â50 years. Hypotheses were tested by regression analysis.The result showed that there are a significant relationshop between employee engagement and job satisfacation and performance. (F = 30.622 ; R = 0.387). Employee engagement has a significant relationship with performance (r = 0.536; p = 0.00), and job satisfaction has significant relationship with performance (r= 0.448; p= 0.00). The results showed that there are an association of employee engagement and job satisfaction with performance.